Analisis Kandungan Rhodamin B pada Produk Perona Pipi (Blush On) yang Beredar di Pasar Tradisional Kota Tarakan - Putri Annisa; Irma Novrianti; Heriani Heriani (Journal Borneo, 2023)
One of the important needs for a woman is cosmetics. One type of cosmetic that teenagers or adult women often use is blush. Blush comes in various colors, and the most popular color is red. It is feared that some cosmetic products may contain harmful red dyes, such as rhodamine B. This research aims to identify the content of rhodamine B compounds in blush products circulating in the Traditional Markets of Tarakan City. The method of this study was a qualitative analysis of the content of the rhodamine B compound in the samples using the rhodamine B Rapid Test Kit. The results showed that from 9 samples of blush circulating in the Traditional Market of Tarakan City, 4 samples of blush were found to be positive for Rhodamin B. From the 4th, 2 positive samples are registered with BPOM.